2018
DOI: 10.1002/hbm.24449
|View full text |Cite
|
Sign up to set email alerts
|

Supervised machine learning quality control for magnetic resonance artifacts in neonatal data sets

Abstract: Quality control (QC) of brain magnetic resonance images (MRI) is an important process requiring a significant amount of manual inspection. Major artifacts, such as severe subject motion, are easy to identify to naïve observers but lack automated identification tools. Clinical trials involving motion‐prone neonates typically pool data to obtain sufficient power, and automated quality control protocols are especially important to safeguard data quality. Current study tested an open source method to detect major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Several studies have suggested that chemotherapy without upfront radiation may be a viable option for patients with grade II oligodendrogliomas [16][17][18]; this also may hold true for patients diagnosed with anaplastic oligodendroglioma [19]. One major benefit of prolonging the use of radiation in patients would be limiting the potential negative long term effects of radiation, including potential cognitive [7,9] and some emerging evidence suggests it may alter wide scale functional connectivity [20]. In our study, the median age of diagnosis was 44, and the median overall survival was not reached at greater than 10 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that chemotherapy without upfront radiation may be a viable option for patients with grade II oligodendrogliomas [16][17][18]; this also may hold true for patients diagnosed with anaplastic oligodendroglioma [19]. One major benefit of prolonging the use of radiation in patients would be limiting the potential negative long term effects of radiation, including potential cognitive [7,9] and some emerging evidence suggests it may alter wide scale functional connectivity [20]. In our study, the median age of diagnosis was 44, and the median overall survival was not reached at greater than 10 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…One of our planned functionalities is to enable real‐time generation of the embedding scatter plots directly within the MRQy HTML front‐end rather than via the backend. Similarly, the Python backend can be easily modified via user‐developed plugins to use a different foreground detection algorithm, compute additional quality measures, or even to integrate quality prediction algorithms 25 in the future. One of the current limitations of MRQy is that it can only be used for quality control of structural MRI data, but we are working on developing new measures that could allow MRQy to be used to interrogate non‐structural MRIs (e.g., diffusion or dynamic contrast‐enhanced MRI).…”
Section: Discussionmentioning
confidence: 99%
“…Quality control of MR imaging has long been a topic of active research, 9,25 but a majority of the resulting tools have been specifically developed for brain MRIs 6,11,12,13,14 in order to identify acceptable scans via supervised learning (based on subjective expert quality ratings). By contrast, MRQy represents a unique solution for quality control of MRI datasets that has been designed to work with scans of any body region while running in an efficient and unsupervised fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, deep learning (DL) approaches have been developed in medical imaging use cases including image reconstruction and artifact reduction (11,12), motion detection and correction (13), and image quality control (14,15). DL methods utilized convolutional neural networks (CNNs) to extract features of different types of artifacts and correct them in brain (16,17), abdominal (18)(19)(20) and cardiac imaging (13).…”
Section: Introductionmentioning
confidence: 99%